Integrated farming system in Kiphire Aspirational District, Nagaland - Ezung, N Khumdemo; Jamir, Temjenna; Sangtam, Litekhing (Indian Farming, 2025)
This article details the success story of transformative impact of an Integrated Farming System (IFS) in Kiphire, Nagaland, led by Shri Chumlongse Sangtam. Starting with maize and rajmah cultivation, Sangtam expanded his farm with technical support from KVK (Kiphire), establishing diverse units like pig breeding, poultry, vermicomposting, and Jalkund for fish and duck rearing. Over time, his farm has become a model IFS farm, enhancing income sustainability, resource efficiency, and resilience. The farm now serves as a resource center, fostering agricultural livelihood, and training. This successful model highlights the potential of IFS in rural prosperity and food security.